2017
DOI: 10.1039/c7nj00428a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of rGO–Zn0.8Cd0.2S via in situ reduction of GO for the realization of a Schottky diode with low barrier height and highly enhanced photoresponsivity

Abstract: Application of rGO–Zn0.8Cd0.2S in Schottky barrier diode with low barrier height and highly enhanced photoresponse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 48 publications
0
61
0
Order By: Relevance
“…As a result mobility increases under illumination as observed previously for rGObased composites at room temperature. 23 It is observed that under illumination the m values have increased by $1.8 times for rGO, $2.5 times for C1, and $10.2 times for C2 compared to dark conditions. Also, this enhancement is almost constant with temperature.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…As a result mobility increases under illumination as observed previously for rGObased composites at room temperature. 23 It is observed that under illumination the m values have increased by $1.8 times for rGO, $2.5 times for C1, and $10.2 times for C2 compared to dark conditions. Also, this enhancement is almost constant with temperature.…”
Section: Resultsmentioning
confidence: 88%
“…20,21 The SCLC model is a very popular method to calculate carrier mobility in rGObased systems. 22,23 In semiconductor transport studies, carrier mobility is considered as an important gure of merit alongside the carrier concentration and conductivity. 24 The nonlinear optical (NLO) properties of GO, rGO and rGOnanomaterial composites have been considerably studied by the scientic community.…”
Section: Introductionmentioning
confidence: 99%
“…However, the materials composited with FeOCl mainly act as carriers rather than semiconductors. Reduced graphene oxide (rGO) nanosheets are an excellent precursor for the immobilization of semiconductors to enhance their catalytic performances, for example, Fe 3 O 4 /rGO, Fe 2 O 3 /rGO, and FeOOH/rGO . Great efforts have been made to use the electrical conductivity of rGO in the Fenton reaction, but the semiconductor characteristics of rGO are often neglected in the photo‐Fenton reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Specific detectivity gives the idea about the potential ability of the material in the field of detector based application. The value obtained for compound 1 is in the order of 10 9 Jones (Table ), which is quite appreciable for a basic schottky diode . Specific detectivity is expressed as trueD*=R()2qID1/2 …”
Section: Resultsmentioning
confidence: 92%